Islamic Economic Politics in Perspective Al-Qur'an and Al-Hadits - Fathurohman, Imron; Karyono, Karyono; Hariyono, Hariyono; Pratiwi, Caswati Rasmi; Rusmanto, Gilang (International Conference on Islamic Studies, 2022)
This research is motivated by the urgency of Islamic Economic Politics in building an economy that aims to ensure the fulfillment of community needs by making the values ​​of Islamic law as a measure. Therefore, it is necessary to have a legal basis from the Qur'an and Al-Hadith that overshadows the implementation of the Islamic Economic Policy. Political Economy of Islam is a government policy that regulates the relationship between the state and society, society with individuals, and individuals with individuals in economic activities. This study uses a qualitative method with a literature study approach, where the data sources in this study were obtained from a literature review in the form of documents, literatures, and other sources those related to this research. The purpose of this study is to determine the definition of Islamic political economy, to know the implementation of Islamic economic politics in economic development, and to know the basis of Islamic economic politics in the Qur'an and Al-Hadith. Islamic Economic Politics is an economic policy, arrangement, or strategy based on Islamic law (sharia) which is used to resolve human affairs in the economic field. The existence of Islamic economic politics is not only aimed at improving the standard of living in a country, but also in every individual primary need of the people can be fulfilled, even allowing them to fulfill their respective secondary needs, because Islamic economic politics always leads to the main economic problem, namely the guarantee of the fulfillment of all economic needs. the primary needs of every individual in society. The implementation of Islamic economic politics is based on Q.S. Al-Hasyr verse 7 as well as several Hadiths of the Prophet SAW., which are relevant to Islamic economic politics.